Fenomena Alternatif Universe (AU) di Medsos Twitter dalam Interaksi Sosial Mahasiswa FISIP ULM - Lubis, Rafa Intan Tiarani; Khairussalam (Prodi Sosiologi FISIP ULM, 2025)
The Alternative Universe (AU) phenomenon on Twitter reflects the growing use of social media among university students as a space for self-expression and the formation of virtual communities through fan fiction, which involves modifying storylines and characters from the originals. This study aims to explore the extent of the AU phenomenon on social media platforms, particularly: 1) Wattpad; and 2) Twitter. Social media influences the patterns of social interaction among students in the FISIP ULM. AU, as a form of digital fiction visualized through screenshots of instant messaging applications and presented in a thread format, has developed into a popular medium of self-expression among teenagers, including university students. With its diverse genres and strong narrative appeal, AU serves not only as entertainment but also as a new communication space that shapes the social dynamics of the campus digital sphere. This research employs a qualitative approach with a phenomenological method, using data collection techniques such as observation, interviews, and documentation. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The findings reveal that students’ involvement in AU strengthens social relations, expands digital friendship networks, and influences their thinking patterns and emotions. AU also functions as a space for experimenting with digital identity and interpreting social issues. The contribution of this study lies in providing a new understanding of AU as a medium for social interaction and self-expression in the digital era. The research recommends that future studies focus on the long-term impact of AU on students’ mental health and their relationships in real life.